Theory of perpendicular arrays - Bierbrauer, Jürgen; Edel, Yves (Journal of combinatorial designs, 1994)
The cryptographical theory of unconditional secrecy and authentication is based on design-like structures called perpendicular arrays in the combinatorial literature. In order to meet the cryptographical requirements some additional and rather natural homogeneity conditions have to be satisfied. We develop a theory of these structures. Topics include bounds on the size, recursive and direct constructions using designs and permutation groups, as well as a link to Room cubes. © 1994 John Wiley & Sons, Inc.
Elektronische Reproduktion der Druck-Ausgabe 14. November 2006
Gesehen am 05.06.2023